The determination of sense organs in Drosophila: a search for interacting genes. - Dambly-Chaudiere, C.; Leyns, L. (International Journal of Developmental Biology, 1992)
The determination of sense organs in Drosophila requires the concerted action of a battery of genes, several of which have been identified. Previous experiments revealed that flies doubly heterozygous for mutations in two of these genes have a reduced number of sense organs, suggesting the existence of a direct interaction between the corresponding genes and/or their products. We have now used this observation to search for mutations in additional genes that would show similar interactions. We have detected 10 recessive mutations that show a dominant reduction in the number of bristles when simultaneously heterozygous for either Df(2)J27 or Df(4)M62f. Among these mutations, 3 are homozygous viable and show striking defects in their bristle patterns, confirming that the genes thus identified play a role in the patterning of sense organs. We conclude that the "gene dose titration" method (Botas et al., 1982) is an efficient method for identifying interacting genes involved in a common process, provided one can identify a well-defined phenotype to look at, and at least one mutation that alters the process. Our experience suggests that its efficiency should be substantially improved by the use of insertional mutagenesis.